PENGARUH PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN, PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Galuh Artika Febriyanti (Politeknik Ubaya, 2020)
The implementation of Good Corporate Governance (GCG) will encourage business people to carry out business practices that prioritize the going concern of the company, the interests of stakeholders, and avoid ways of gaining instant profits that are detrimental to others so as to create fair competition and a conducive business climate. Good Corporate Governance (GCG) implemented by companies in Indonesia is very important to support economic growth and stability. Research on earnings management has been carried out both overseas and domestically. But it was found that there was a research gap in previous studies. This research was conducted because of the gap research phenomenon from previous studies. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2015-2018 with a sample of 57 companies. The results showed that company growth and company size did not have a significant effect on earnings management. While tax planning has a significant influence on earnings management. This research shows that Good Corporate Governance does not moderate the relationship between company size and earnings management. Good Corporate Governance also does not moderate the relationship between tax planning and earnings management.